STRUCTURE OF THE ELECTRONIC MEDICAL RECORD AND ITS COMPONENTS (Eureka Journal of Computing Science & Digital Innovation, 2026)
Electronic Medical Records (EMRs) are digital repositories of patient health information designed to improve the accessibility, accuracy, and continuity of healthcare delivery. EMRs typically include structured demographic data, comprehensive medical histories, clinical documentation, diagnostic results, treatment plans, and physician observations, enabling efficient clinical decision-making and patient management. According to existing literature, the structure of EMRs encompasses both longitudinal patient data collected over time and standardized clinical components that facilitate interoperability across healthcare systems. However, research also highlights variability in data structure and the ongoing need for standardized clinical data formats to support effective data exchange and integration. The adoption of EMRs has been associated with improvements in healthcare structure and processes, though the evidence on clinical outcomes remains complex. EMRs play a pivotal role in enhancing coordination of care, reducing medical errors, and supporting evidence-based practices in modern health information systems.
Keywords: Electronic Medical Record (EMR); Medical data; Personal information; Medical history; Instrumental tests; Interoperability